Evaluating the impact of curriculum model choices on academic success for extended commerce degree programmes - Ontong, J. M.; Bruwer, A. (South African Journal of Higher Education, 2024)
Understanding how curriculum design choices impact the academic success in terms of grades of students provides valuable insights into the effective delivery of the teaching of introductory financial accounting and economics for students in extended degree programmes (ECP). The main research question asks which delivery model, either foundational modules or augmented main-stream modules, provides an effective pathway to achieving academic success in terms of grades in ECP. Performing a qualitative analysis of a large dataset incorporating 11 410 observations of data of a ten-year period. Analysis of variance was used to identify which delivery model is the most effective in terms of students’ performance. The study provides evidence that introductory modules may provide increased support compared to augmented modules for financial accounting. The study also shows that the use of an introductory module has a significant beneficial effect on extended programme students in their second year in order to achieve academic success in mainstream modules but only in certain cases only if a certain threshold is achieved in the introductory module. This threshold appears to be higher in foundational level economics than financial accounting. The study provides evidence that the choice of delivery model has an impact on financial accounting and economics students’ performance in terms of grades achieved. Foundation modules may benefit from higher required pass grade thresholds so that students in ECP are able to ultimately obtain their degrees.